2020
DOI: 10.1016/j.jpain.2019.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptor Interleukin 33 Receptor/ST2 Signaling in Vibration-Induced Muscle Pain in the Rat

Abstract: Occupational exposure to mechanical vibration can produce the hand-arm vibration syndrome (HAVS), whose most disabling symptom is persistent muscle pain. Unfortunately, the pathophysiology of HAVS pain is still poorly understood, precluding the development of mechanism-based therapies. Since interleukin 33 (IL-33) is essential for inflammation and recovery that follows skeletal muscle injury, we explored its role in muscle pain in a model of HAVS, in adult male rats. Concomitant to mechanical hyperalgesia, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…However, it is noteworthy that mechanical hypersensitivity evoked by 20 ng of IL-33 in naive rats is weaker than that induced by SNI at 1 week, although this dose is similar to the amount of IL-33 expressed in the RN of SNI rats, implying some molecules excepting IL-33 may be also involved in the early development of mononeuropathic pain. Our findings are in accord with previously reported that administration of exogenous IL-33 to normal animals induces pain hypersensitivity, while blocking IL-33/ST2 signaling inhibits pathological pain [ 39 , 43 , 44 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, it is noteworthy that mechanical hypersensitivity evoked by 20 ng of IL-33 in naive rats is weaker than that induced by SNI at 1 week, although this dose is similar to the amount of IL-33 expressed in the RN of SNI rats, implying some molecules excepting IL-33 may be also involved in the early development of mononeuropathic pain. Our findings are in accord with previously reported that administration of exogenous IL-33 to normal animals induces pain hypersensitivity, while blocking IL-33/ST2 signaling inhibits pathological pain [ 39 , 43 , 44 ].…”
Section: Discussionsupporting
confidence: 93%
“…We were particular interested in Il-33 , which has not previously been implicated in gout pain, but implicated in some other pain conditions, including neuropathic, cancer and muscle pain, etc. 18 , 19 Therefore, we set to examine the possible involvement of IL-33 in mediating the pain response of the mouse gout model.…”
Section: Resultsmentioning
confidence: 99%
“…IL-33, a member of the IL-1 family, binds to the receptor complex, consisting of IL-33 specific ST2 and IL-1 receptor accessory protein IL-1RAcp, to elicit biological functions in inflammation, autoimmune response and homeostasis 16 , 17 . Recent evidence suggests that IL-33 can act as an important pain mediator in certain pain conditions, including joint pain, bone cancer pain, muscle pain and neuropathic pain 12 , 18 , 19 . Our recent work further identified IL-33 engages with ST2 in peripheral sensory neurons to exert sensory neuron hyperexcitability 20 , 21 .…”
Section: Introductionmentioning
confidence: 99%
“…The percentage decrease in Tmem120A expression was calculated as: (normalized density for AS/normalized density for MM x 100) À 100. 3,5…”
Section: Sds-page and Western Blottingmentioning
confidence: 99%